Successful Treatment of Cor Pulmonale in Drug-Resistant Tuberculosis-Related ARDS: A Case Report - Amalia Sutoyo (Jurnal Respirasi, 2025)
Introduction: One of the biggest challenges in global tuberculosis (TB) control is the spread of drug-resistant TB. Chronic cor pulmonale is confirmed in a pulmonary TB patient through the mechanism of pulmonary hypertension (PH). Tuberculosis is one of the causes of respiratory failure requiring mechanical ventilation. However, cases of TB requiring mechanical ventilation as the primary cause of respiratory failure are rare. Tuberculous acute respiratory distress syndrome (ARDS) is rare, but it has a very poor prognosis when it does occur. Case: A 48-year-old female arrived with chronic cor pulmonale decompensated symptoms with drug-resistant pulmonary TB diagnosed by echocardiography. The patient developed ARDS during treatment. Initially, the patient was treated with loop diuretics, oxygen treatment, vasodilators, digitalis, anticoagulant medication, bronchodilators, and empirical antibiotics. As her condition deteriorated, the patient was put on mechanical ventilation and anti-TB medication. The patient’s health improved, and she was allowed to return home. Conclusion: Acute respiratory distress syndrome patients associated with drug-resistant TB may experience decompensated chronic cor pulmonale. In this instance, the main diagnostic method for cor pulmonale is echocardiography. Seldom is drug-resistant pulmonary TB associated with ARDS that results in cor pulmonale being documented. Positive results are linked to early diagnosis and treatment. Following therapy, the patient’s health improved, and the patient was permitted to return home with the prescribed drugs.